Negative voltage surge resistant circuit design in HVIC. Issue 23 (1st November 2013) - Zhu, Jing; Sun, Guodong; Sun, Weifeng; Zhang, Yunwu
Abstract : A reliable and methodical solution to restrain transient undershoot on VS pin for a high‐voltage gate drive circuit with a transient negative voltage detector circuit (TNVDC) is proposed. The proposed TNVDC circuit does not consume any quiescent current while the chip works normally and it is totally integrated in a high‐voltage integrated circuit (HVIC) without any additional discrete devices in the system. The proposed circuit could send a control signal to the drive stage of the HVIC for decreasing the sink current while the transient undershoot of the VS is excessive. The measurement shows that the negative voltage surge tolerance is −98 V of the HVIC with TNVDC.